2008
DOI: 10.1593/neo.08162
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vascularity Assessed By Magnetic Resonance Imaging and Intravital Microscopy Imaging

Abstract: Gadopentetate dimeglumine (Gd-DTPA)-based dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is considered to be a useful method for characterizing the vascularity of tumors. However, detailed studies of experimental tumors comparing DCE-MRI-derived parametric images with images of the morphology and function of the microvascular network have not been reported. In this communication, we describe a novel MR-compatible mouse dorsal window chamber and report comparative DCE-MRI and intravital microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 30 publications
1
69
0
Order By: Relevance
“…EXTRACTING INFORMATION about the architecture of microvascular beds is extremely important for understanding tissue oxygenation and metabolism of well-perfused organs (brain (1,2), myocardium (3), skeletal muscle (4)), as well as for investigating numerous pathologies such as vascular dementia (5) or tumor angiogenesis (6,7). While intravital microscopy can probe the microcirculation in superficial tissues (8), magnetic resonance imaging (MRI) can probe functionally relevant properties of the microcirculation of living tissues deep within the body (6) using various contrast agents or signal mechanisms.…”
mentioning
confidence: 99%
“…EXTRACTING INFORMATION about the architecture of microvascular beds is extremely important for understanding tissue oxygenation and metabolism of well-perfused organs (brain (1,2), myocardium (3), skeletal muscle (4)), as well as for investigating numerous pathologies such as vascular dementia (5) or tumor angiogenesis (6,7). While intravital microscopy can probe the microcirculation in superficial tissues (8), magnetic resonance imaging (MRI) can probe functionally relevant properties of the microcirculation of living tissues deep within the body (6) using various contrast agents or signal mechanisms.…”
mentioning
confidence: 99%
“…Positive correlations were found between and EESF obtained by invasive imaging. Gaustad et al [25] investigated whether Gd-DTPA-based DCE-MRI can be a useful method for characterizing vascularity of tumors by comparing the images of ⋅ as obtained by Kety analysis with Blood Supply Time (BST) images (i.e., images of the time from when arterial blood enters a tumor through the supplying artery until it reaches a vessel segment within the tumor) and morphologic images of the microvascular network which were produced by intravital microscopy. They found that the ⋅ images mirrored the morphology (microvascular density) and the function (BST) of the microvascular networks well.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, nonmetallic chambers composed of polymer materials have been fabricated, which can be applied to studies employing ionising or non-ionising radiation in animal exposure experiments without inducing thermal effects (Ushiyama et al, 2004). Moreover, they are compatible for magnetic resonance imaging (MRI) (Gaustad et al, 2008;Erten et al, 2010).…”
Section: Characteristics Of the Dorsal Skinfold Chamber Modelmentioning
confidence: 99%